(3TeS GdYdhe hOhGA cdGe GdYQH ef Gdcdhes - (3fThGf Hf SYjO GdMejQj, CHh SYjO,J (B573 (3g` s ((3GdMSf Hf CMeO GdfcfGai s)
(3BNQgG (B:s
(3hjbGd Ef CUdg ef ESJNGQg GdVHY , hgh Cf jLYd Ydi ae hLGQgG NTHI MJi jNQL ef ehVY BNQ GSJNGd ef GdNjdGA (B( (3GdJaYjd (B) (3, hJNjQ GdTF Ci GNJGQg s
(3HgG fXGe GdJYbjHIs
(3JJab ai ChdgG eY GdLRA GdChd ef fSNI NRGfI GdEeGe jMji Hf eMeO Hf jMji (B- (3UfYGAs
(3fSNI SGOSIs
(3hbO fbdgG GdfGSN ef fSNI JeJ cJGHJgG SfI (B1136 (3g` s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3GddZIs